In between [videorecording (DVD)] - Hamoud, Maysaloun, 1982-; Hawa, Mouna; Kanboura, Shaden; Jammalieh, Sana (Film Movement series., 2018)
Lalia (Mouna Hawa), Salma (Sana Jammelieh), and Nur (Shaden Kanboura) share an apartment in the vibrant heart of Tel Aviv. Lalia, a criminal lawyer with a wicked wit, loves to burn off her workday stress in the underground club scene. Salma, slightly more subdued, is a DJ and bartender. Nur is a younger, religious Muslim girl who moves into the apartment in order to study at the university. Nur is both intrigued and intimidated by her two sophisticated roommates. When her conservative fiance visits, he is horrified by her secular friends, entreating her to hasten their marriage, leave Tel Aviv, and assume her rightful role as a wife. She refuses, and his violent rebuttal leaves all of the women shaken. Salma and Lalia also face turmoil: Lalia has found love with a modern Muslim man whose acceptance proves less than unconditional, and Salma discovers that her Christian family in a northern Galilean village is not as liberal as they claim. These three very different women find themselves doing the same balancing act between tradition and modernity, citizenship and culture, fealty and freedom.